SWINDLERT©: Development of Augmented Reality Game-Based Interactivity for Enhancing Cybercrime Awareness - Sakinah Ali Pitchay; A.H Azni; Farida Hazwani Mohd Ridzuan; Najwa Hayaati Mohd Alwi; Muhammad Syahmi Imran (UiTM Press, Universiti Teknologi MARA, 2025)
Indexed